Pelaksanaan user education sebagai upaya promosi perpustakaan pada UPT. Perpustakaan Universitas Malikussaleh Lhokseumawe - Labibah Labibah; Uci Elisa Pitri (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2022)
The library is a service unit that becomes a source of information that has great power because it covers a variety of science ranging from economics, politics, art, health and other sciences. As we know that the library is important for us to introduce to the community, especially to students or students who are very necessary to support the education that is being pursued. One way that can be done to introduce the library is to hold a library promotion ucer education program created by the library to bridge between the library and its library and as one way or strategy to promote the library. This article discusses the implementation of ucer education in upt malikussaleh university library using lecture methods, audio / videovisual, demonstrations or demonstrations and also the library playbook. The obstacle faced is still the lack of librarian knowledge about the importance of ucer education activities in the library and also constrained at the time and location. Efforts that can be done is to provide an understanding of the importance of the implementation of ucer education in the library to library personnel and librarians in the library and should ucer education also be done online.